2011
DOI: 10.1021/la200961a
|View full text |Cite
|
Sign up to set email alerts
|

The Adsorption and Self-Assembly of Mixtures of Alkylbenzene Sulfonate Isomers and the Role of Divalent Electrolyte

Abstract: In this paper, the role of the different structural isomers of the anionic surfactant sodium para-dodecyl benzene sulfonate, LAS, on surface adsorption and solution self-assembly has been studied. Using a combination of neutron reflectivity, NR, and small angle neutron scattering, SANS, the effect of mixing an isomer with a short symmetric hydrocarbon chain with one which has an asymmetric hydrocarbon chain on both the equilibrium surface adsorption behavior and the solution microstructure of the mixtures, bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
32
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 23 publications
(58 reference statements)
6
32
0
Order By: Relevance
“…Therefore, this model does not fit the data (electronic supplementary material, figure S3). Furthermore, earlier works [28,29] suggest that surfactants' micelle diameter are usually twice the thickness of the adsorption layer, which indicates that it has to be the individual molecules rather than their aggregates that adsorb to the interface. A previous study [28] found that at pH 7.5 surfactin adopts a ball-like structure with a thickness of 14 Å at the air/ water interface and the overall structure of the adsorbed surfactin layer appears to be identical to a thickness of 15 Å at a hydrophobic octadecyltrichlorosilane-coated silicon surface.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, this model does not fit the data (electronic supplementary material, figure S3). Furthermore, earlier works [28,29] suggest that surfactants' micelle diameter are usually twice the thickness of the adsorption layer, which indicates that it has to be the individual molecules rather than their aggregates that adsorb to the interface. A previous study [28] found that at pH 7.5 surfactin adopts a ball-like structure with a thickness of 14 Å at the air/ water interface and the overall structure of the adsorbed surfactin layer appears to be identical to a thickness of 15 Å at a hydrophobic octadecyltrichlorosilane-coated silicon surface.…”
Section: Resultsmentioning
confidence: 99%
“…The predicted curves for small micelles (n ¼ 3) are shown in electronic supplementary material, figure S4 and for bigger micelles (n ¼ 20) in electronic supplementary material, figure S5. According to the work of Shen et al [28] and Tucker et al [29], we apply the different values of n for the surfactants as in table 2. For the SCBS surfactants, which are the homologue of sodium dodecyl benzene sulfonate with four more carbon atoms, the size of aggregates in the bulk solution is around 100 nm, which indicates a large aggregation number [27].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, mixed surfactant systems exhibit more pronounced interfacial adsorption than single surfactant systems [7]. Furthermore, the addition of an electrolyte to a mixed surfactant solution significantly may increase the concentration of surfactant adsorbed at the interface compared with the solution in the absence of electrolyte [9,10,14]. In such cases, surfactant is observed to adsorb not only as a monolayer at an interface but as a multilayer structure that extends into the bulk beneath the interface [9].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we present a mathematical model for the self-assembly of surfactant in a multilayer structure such as those observed in [9,10,14], neglecting the effect of any counterions that may be present and any bulk solution effects such as aggregation. We consider two situations: (i) the adsorption of a surfactant multilayer at an interface and (ii) the adsorption of a surfactant solution onto two surfaces that are in close proximity to one another.…”
Section: Introductionmentioning
confidence: 99%